Evaluation of Wetland Environmental Awareness Among Biology Students - Cahayani, Kania Putri; Utami, Nurul Hidayati (Universitas Lambung Mangkurat, 2024)
Environmental awareness refers to the importance of maintaining a clean and healthy environment. This awareness is reflected in an individual's attitudes and actions, especially when they act voluntarily without external pressure. The Biology Education program at Universitas Lambung Mangkurat (ULM) envisions becoming a leading and competitive study program that produces graduates with expertise as educators who possess an in-depth understanding of wetland environments. This vision aims to produce graduates who not only have educational skills but also understand environmental issues, especially in wetland management and preservation, and have a high level of environmental awareness to support the sustainability of ecosystems. This study aims to describe the wetland environmental awareness of the Biology Education students at ULM. The method used is a quantitative survey conducted among active Biology Education students at ULM, consisting of students from the 2022, 2023, and 2024 academic years. The research results show that the students' environmental awareness is categorized into high (15.48%) and moderate (84.52%) criteria. The moderate environmental awareness level suggests a decline in environmental consciousness among students, which could affect the next generation's awareness if not balanced with environmental awareness.